Science as a Psychological Approach: A Critical Analytical View of Science in its Psychological Dimensions - Nyan, Saleh (Al-Mukhtar Journal of Social Sciences, 2025)
This research aims to shed light on the psychological dimension in scientific practice. The core issue (research problem) was represented in the following question: Is science an activity conducted according to strict mechanical rules (adhering to the scientific method and achieving the goals of understanding and explanation), such that it cannot be viewed outside of this framework, or are there other psychological dimensions that influence this practice, thereby forming another perspective through which science can be understood? The researcher addressed this topic in an introduction, three sections, and a set of conclusions. The first section is titled: "Psychological Motivations in the Structure of Scientific Practices.". The second section: "Psychological Barriers to Practicing Science." The third section: "Psychological Conflicts.". The researcher arrived at several conclusions, generally crystallizing in the idea that science has additional psychological (mental) dimensions that go beyond its method (the scientific method) and its goals (understanding, explanation, prediction, control, and regulation). These dimensions represent an angle through which scientific practices can be viewed, thus providing an approach for understanding the essence of science.
Keywords: Perspective; Approach; Psychology